ADR in Business : - Goldsmith, J.C. (Kluwer Law International, 2006)
The purpose of this book is precisely to look at ADR on its own terms as a way of resolving business disputes, particularly at the international level. Drawing upon diverse approaches, ADR experts from a variety of countries explore the situations to which ADR lends itself and the different permutations it offers to allow each dispute to be handled in the manner most fitting to the circumstances. The contributors also show how ADR serves such important considerations as the interests involved, the need to avoid a public display of differences, and the wish to anticipate problems